Student reflections on an online orientation programme for first-year students in an institution of higher education - Hoskin, Ruth; Rama, Sharmla; Dansoh, William (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2026)
The First-Year Experience Programme (FYEP) is significant as it forms the foundation of the entire university experience. This article aims to highlight first-time entry undergraduate (FTEN) students’ reflections on the online orientation programme in the College of Humanities. As part of the FYEP, the College delivered a 23-day recurring online orientation programme in February 2024. Student evaluations of any programme, whether curricular or co-curricular, are important monitoring and evaluation methods to ensure the student experience is enhanced. An equally important reason for documenting student reflections on the orientation programme is to analyse the data generated by the student evaluation tool. Such data are important for understanding how first-year students experience institutional student support programmes and how their participation facilitates their transition into university life. In this paper, transition is conceptualised as a complex phenomenon during which FTENs are supported to adjust to the university environment, establish new relationships with peers and university staff, and integrate into the university community as successful students. A total of 343 out of 879 first-year students who participated in the online orientation programme completed the evaluation survey, which sought to determine the extent of student satisfaction with the programme and how it could be improved. The survey included both closed and open questions, yielding quantitative and qualitative data. The data were analysed using thematic content analysis and the SPSS data analysis programme. The majority of participants (75%) expressed overall satisfaction with the programme. Qualitative responses on ways to improve the programme included addressing technology infrastructure and students’ digital literacy challenges, time management, the use of isiZulu, and a preference for contact rather than online orientation. It is recommended that the university and the Department of Higher Education and Training explore ways to expose school learners to university environments virtually during the pre-registration phase to bridge the school-university gap. In addition, innovative ways to improve pre-entry first-year students’ digital literacy skills to minimise the risk of technology becoming a barrier to a successful transition should be explored. The adoption of a blended approach (online and physical) to orientation should be considered
Journal article published in African Perspectives of Research in Teaching and Learning Journal Volume 10, Issue 1, 2026
Keywords: Digital literacy; Higher education; Online orientation programme evaluation; School-university gap; Student experiences; Education, higher; Computer literacy; Library orientation -- Technological innovations; Libraries and the Internet; College student orientation; College freshmen